(untitled) (The Review of Diabetic Studies, 2025)
Introduction: Post-discharge monitoring is essential for patients recovering from cardiac events, as it reduces readmission rates, improves long-term recovery, and enhances quality of life. Traditional nursing care generally involves in-person follow-up visits to monitor recovery, whereas technology-assisted telehealth interventions offer continuous monitoring, real-time data sharing, and more flexible patient interaction. This study compares the effectiveness of traditional nursing care versus technology-assisted telehealth interventions in managing post-discharge cardiac recovery. Objective: To evaluate the impact of traditional nursing care versus technology-assisted telehealth interventions on post-discharge recovery in cardiac patients, focusing on readmission rates, health outcomes, and patient satisfaction. Methodology: A cohort of 420 cardiac patients was divided into two groups: one received traditional nursing care, while the other utilized telehealth interventions. Health outcomes, readmission rates, and patient satisfaction were assessed over a 6-month period. Statistical analysis included chi-square tests, t-tests, and Kaplan-Meier survival analysis. Results: The telehealth group showed a 30% reduction in readmission rates and significant improvements in health outcomes, including physical activity, symptom control, and quality of life compared to traditional nursing care. Telehealth patients also reported higher satisfaction scores. Conclusion: Technology-assisted telehealth interventions have shown a marked advantage in reducing readmissions and improving patient satisfaction, highlighting the potential for telehealth to complement or replace traditional care approaches in post-discharge cardiac care.